Productivity, Nutrient Composition, and Hydrocyanic Acid Concentration of Super-2 Forage Sorghum at Different NPK Levels and Planting Spaces - D. Astuti; B. Suhartanto; N. Umami; A. Irawan (Faculty of Animal Science, Bogor Agricultural University, 2019)
Low digestibility and toxicity of hydrocyanic acid (HCN) in sorghum forage are disadvantage for ruminant. Appropriate fertilizer application and planting strategy can improve sorghum yield and quality. A field experiment was aimed to investigate the productivity, nutrients content, and HCN concentration of Super-2 forage sorghum (Sorghum bicolor (L) Moench) at different planting spaces and levels of NPK fertilizer. The seeds were planted according to 3×3 factorial design in which the first factor was planting space (J1= 90×20 cm, J2= 75×25 cm, and J3= 60×30 cm) and the second factor was three levels of NPK fertilizer (P1= 0 kg/ha; P2= 100 kg/ha; and P3= 200 kg/ha, respectively). Crude protein (CP), crude fiber (CF), and HCN concentration were affected by the interaction of NPK levels × planting spaces (p<0.05). The CP and HCN content increased as NPK levels increased at all planting space patterns while CF content decreased. NPK fertilizer application significantly increased yield production (DM, OM, and CP productions), whereas planting space treatment did not show any improvement except for CF that significantly lower on 60×30 cm planting space. Sorghum receiving 200 kg/ha of NPK at 60×30 cm planting space produced the highest CP and the lowest CF content, resulting in the highest OM and CP biomass production. In conclusion, NPK fertilizer significantly improved productivity and nutrients composition and in the same way, also increased HCN concentration of sorghum Super-2 varieties.